Application of the food-energy-water nexus to six seafood supply chains: hearing from wild and farmed seafood supply chain actors in the United States, Norway, and Vietnam - Fry, Jillian P.; Scroggins, Rachel E.; Garlock, Taryn M.; Love, David C.; Asche, Frank; Brown, Mark T.; Nussbaumer, Elizabeth M.; Nguyen, Ly; Jenkins, Lekelia D.; Anderson, James; Neff, Roni A. (Frontiers in Sustainable Food Systems, 2024)
The food-energy-water (FEW) nexus highlights the interdependencies between the systems that people rely on for these essential resources. For example, globally, over two thirds of freshwater withdrawals are used to produce food, and another 10% is used during energy generation. In addition, the food system uses one eighth of global net energy. Seafood is a nutritionally important food, and it is critical to use freshwater and energy resources efficiently throughout seafood supply chains to safeguard future supplies and to reduce environmental impacts. Identifying scalable opportunities to improve resource use in this sector is challenging due to diverse production methods and settings. The diversity in production methods results in highly variable resource use across supply chains, which may contribute to siloed efforts within supply chains to improve efficiency, instead of larger efforts that involve multiple seafood supply chains. Additionally, efforts to develop and implement efficiency strategies must be informed by fishers, aquaculturists, processors, and other seafood supply chain actors to avoid investing time and resources into strategies that will have low uptake. A